Kontribusi Customer Service Dalam Mengatasi Keluhan Untuk Meningkatkan Kepuasan Nasabah PT. Bank Sumut Syariah Kantor Cabang Medan Katamso - Ramdanil Fajar; Atika Atika (Akubis : Jurnal Akuntansi dan Bisnis, 2023)
In banking, frontliner officers are required to be able to provide good service and must provide satisfaction for customers. Customer satisfaction is a top priority in this study because currently the level of competition is getting tougher among Islamic banks in Medan Katamso. The main thing that must be done by Bank Sumut Syariah Medan Katamso Branch Office in order to be able to retain loyal customers, the banking sector must be able to provide good service for the problems faced by each of its customers regardless of the customer's social status. The technique used in this research is qualitative by using descriptive analysis. Whereas in this study using the formulation of the problem, among others, how is the contribution of Customer Service in overcoming complaints to increase customer satisfaction at Bank Sumut Syariah Medan Katamso Branch Office? Constraints faced by Customer Service in handling customer complaints? and the purpose of this research is to describe the contribution of Customer Service, besides that the writer also wants to know the obstacles faced by customers and how the solutions provided by Customer Service at Bank Sumut Syariah Medan Katamso Branch Office for the problems faced by customers so that they can make customers stay loyal. While the object of this research is customer complaints. Here the researcher goes directly to the field to conduct observations, interviews and documentation of the data that researchers need to find out how the process of handling customer complaints at Bank Sumut Syariah Medan Katamso Branch Office with the theory in principle is the same, namely the same - the same to solve problems faced by customers. The results in this study indicate that the Bank of North Sumatra Syariah Medan Katamso Branch Office in solving the problems experienced by customers is by using data reduction analysis techniques, presenting data and drawing conclusions and after conducting research the customer service can solve the problem by cross selling to customers, so that customers are clearer about the problems they face and at the same time explain about the products owned by Bank Sumut Syariah Medan Katamso Branch Office.